Overexpression of MAPK15 in gastric cancer is associated with copy number gain and contributes to the stability of c-Jun - Jin, Dong-Hao (Oncotarget, 2015)
This study was aimed at understanding the functional and clinicopathological significance of MAPK15 alteration in gastric cancer. Genome-wide copy number alterations (CNAs) were first investigated in 40 gastric cancers using Agilent aCGH-244K or aCGH-400K, and copy number gains of MAPK15 found in aCGH were validated in another set of 48 gastric cancer tissues. The expression of MAPK15 was analyzed using immunohistochemistry in concurrent lesions of normal, adenoma, and carcinoma from additional 45 gastric cancer patients. The effects of MAPK15 on cell cycle, c-Jun phosphorylation, and mRNA stability were analyzed in gastric cancer cells. Copy number gains of MAPK15 were found in 15 (17%) of 88 tumor tissues. The mRNA levels of MAPK15 were relatively high in the gastric cancer tissues and gastric cancer cells with higher copy number gains than those without. Knockdown of MAPK15 using siRNA in gastric cancer cells significantly suppressed cell proliferation and resulted in cell cycle arrest at G(1)-S phase. Reduced c-Jun phosphorylation and c-Jun half-life were observed in MAPK15-knockdowned cells. In addition, transient transfection of MAPK15 into AGS gastric cancer cells with low copy number resulted in an increase of c-Jun phosphorylation and stability. The overexpression of MAPK15 occurred at a high frequency in carcinomas (37%) compared to concurrent normal tissues (2%) and adenomas (21%). In conclusion, the present study suggests that MAPK15 overexpression may contribute to the malignant transformation of gastric mucosa by prolonging the stability of c-Jun. And, patients with copy number gain of MAPK15 in normal or premalignant tissues of stomach may have a chance to progress to invasive cancer.